Obtaining powdered sweet potato in spouted bed and influence of drying temperature on physicochemical properties (Research, Society and Development, 2020)
The present study aimed to obtain the sweet potato flour through the spray drying process, in a spouted bed and to evaluate the effect of the temperatures used on its physical-chemical properties. The sweet potato was submitted to the spouting bed drying process at temperatures of 50, 60 and 70 °C, air flow in the atomizing nozzle of 3.0 m3/min and pump flow rate of 2.7 ml/min. The fresh sweet potatoes and the flours obtained were characterized according to the following physical-chemical parameters: humidity, total solids, water activity (aw), ash, lipids, carbohydrates, pH, total tileable acidity (ATT), total soluble solids (SST) and ratio (SST/ATT ash when there was an increase in the drying temperature. The drying allowed a reduction in the moisture content, water activity of fresh sweet potatoes, guaranteeing a longer shelf life of the product. There was). The sweet potato in natura showed a high moisture content of 69.48% and an increase in the contents of statistically significant differences between the temperatures used in relation to the physical-chemical parameters. However, the temperature of 80 °C enabled the highest value of total soluble solids, ratio (SST/ATT) and total carbohydrates, showing the technological potential of the powder product.